Adding Enzalutamide to First-Line Treatment for Metastatic Hormone-Sensitive Prostate Cancer: A Cost-Effectiveness Analysis - Zhang, Peng-Fei; Xie, Dan; Li, Qiu (Frontiers in Public Health, 2021)
Background The aim of this study is to evaluate the pharmacoeconomic profile of adding enzalutamide to first-line treatment for metastatic, hormone-sensitive prostate cancer (mHSPC) from the US and Chinese payers’ perspectives. Materials and Methods A Markov model with three health states: progression-free survival (PFS), progressive disease (PD) and death, was constructed. All patients were assumed to enter the model in the PFS state and transit according to the transition structure. Efficacy data were derived from the ENZAMET trial and Weibull distribution curves were modeled to fit the survival curves. Costs in the model included cost of drugs, best-supportive care (BSC), follow-up, tests and adverse events (AEs)-related treatments. The primary endpoint of the study was incremental cost-effectiveness ratio (ICER). In addition, the impact of several key parameters on the results of the cost-effectiveness analysis was tested with one-way sensitivity analyses and probabilistic sensitivity analyses. Results Overall, ICERs were $430,933.95/QALY and $225,444.74/QALY of addition of enzalutamide to androgen deprivation therapy (ADT) versus ADT from the US and Chinese payers’ perspective, respectively. The most influential factors were the utility for the PFS state and the cost of enzalutamide. At the willingness-to-pay (WTP) thresholds of $100,000.00/QALY in the US and $28,988.40/QALY in China, the probability of adding enzalutamide to first-line treatment being a cost-effective option for mHSPC was 0%. Conclusions Based on the data from the ENZAMET trial and the current price of enzalutamide, adding enzalutamide to first-line treatment is not cost-effective for patients with mHSPC from the US and Chinse payers’ perspectives.